Удмурт калык кырӟанъёс - Ложкин Ф. А. (Национальная библиотека Удмуртской Республики, 2016)
Режим доступа: http://elibrary.unatlib.org.ru/handle/123456789/29140 Экземпляры: НЭБ (20161212) / Инвентарный номер: PDF004701 / Сис.шифр: 783 / Авт.знак: У 30 / ГРНТИ: 18 / ББК: 85